Factors influencing consumer’s green purchasing behaviour towards green products in Malaysia / Syed Muhammad Yusof Syed Ahmad Badiuzaman - Syed Ahmad Badiuzaman, Syed Muhammad Yusof (Faculty of Business and Management, 2018)
Today, rapid development of technology has caused both positive or negative affect and changes in the environment. While enjoying the convenience provided by technology, people should have the right mind-set in keeping and protecting their environment healthy. Therefore, the aim to conduct this study is to examine the factors that influence consumers‟ green purchase behaviour towards green products in Malaysia. There are 4 independent variables were used in this research project to identify the factors that influence consumers‟ purchasing behaviour toward green products; Environmentalism, Behaving Economically, Knowledge and dependent variable; Green Purchasing Behaviour. 100 Malaysia consumer are the minimum sole targeted respondents in this study. It is found that there are no significant differences for the gender and race variables whereas monthly income variable was found a significant difference on it. In addition, the study findings also discovered that there is a significant relationship between the factors influence and consumers‟ purchasing behaviour towards green products. Consequently, these research findings have provided some insight and feedback to businesses who basically facing a lot of challenges in convincing consumers to purchase green products. By gathering this information, marketers can understand the route that shifts the environmental factors to green purchase behaviour. They also would be able to formulating their various strategies to effectively attract the Malaysian consumers to purchase green products.